2019
DOI: 10.14814/phy2.14256
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic D1 receptor effects on commissural inputs targeting layer V pyramidal subtypes of the mouse medial prefrontal cortex

Abstract: In humans, prefrontal cortical areas are known to support goal‐directed behaviors, mediating a variety of functions that render behavior more flexible in the face of changing environmental demands. In mice, these functions are mediated by homologous regions within medial prefrontal cortex (mPFC) and rely heavily on proper dopaminergic tone. Comprised of two major subtypes, pyramidal tract (PT) and intratelencephalic (IT), layer V pyramidal cells serve as the major outputs of the mPFC, targeting brainstem nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Type I and type II layer V pyramidal cells were characterized based on their baseline physiological properties including the presence of a hyperpolarization activated cationic current (“sag”) and/or the presence of a spike afterdepolarization (ADP)/spiking doublet. As shown by others ( Dembrow et al, 2010 ; Spindle and Thomas, 2014 ; Leyrer-Jackson and Thomas, 2017 , 2018 , 2019 ), type I and type II cells did not differ in cellular capacitance (type I: 23.7 ± 0.4 pA, type II: 24.8 ± 1.3 pA; p > 0.05; Figure 2A ) or resting membrane potential (type I: −67.7 ± 0.5 mV, type II: −68.2 ± 0.5 mV; p > 0.05; Figure 2B ). Representative traces depicting action potential firing of a type I and type II cell are shown in Figures 2C,D .…”
Section: Resultssupporting
confidence: 61%
“…Type I and type II layer V pyramidal cells were characterized based on their baseline physiological properties including the presence of a hyperpolarization activated cationic current (“sag”) and/or the presence of a spike afterdepolarization (ADP)/spiking doublet. As shown by others ( Dembrow et al, 2010 ; Spindle and Thomas, 2014 ; Leyrer-Jackson and Thomas, 2017 , 2018 , 2019 ), type I and type II cells did not differ in cellular capacitance (type I: 23.7 ± 0.4 pA, type II: 24.8 ± 1.3 pA; p > 0.05; Figure 2A ) or resting membrane potential (type I: −67.7 ± 0.5 mV, type II: −68.2 ± 0.5 mV; p > 0.05; Figure 2B ). Representative traces depicting action potential firing of a type I and type II cell are shown in Figures 2C,D .…”
Section: Resultssupporting
confidence: 61%
“…The differential expression of many protein types contributes to the varied transcriptomes of pyramidal cells, but G protein-coupled receptors (GPCRs) represent exciting candidate molecules that may modify synaptic strength and plasticity following EtOH exposure. For example, several studies have demonstrated that the dopamine D1 and dopamine D2 receptors guide distinct effects on ET versus IT pyramidal cells (Anastasiades et al, 2019;Clarkson et al, 2017;Gee et al, 2012;Leyrer-Jackson and Thomas, 2019;Seong and Carter, 2012). Perhaps oscillations in PFC dopamine during EtOH experiences facilitate varied synaptic adaptations based on cell type-specific expression of dopamine receptors.…”
Section: Discussionmentioning
confidence: 99%
“…IT neurons generally display narrow or limited dendritic arborizations and have been described as type B neurons. In addition to these anatomical and structural differences, several membrane physiology parameters of ET type A and IT type B pyramidal cells diverge in a distinguishing manner (Anastasiades et al, 2019, 2018; Collins et al, 2018; Dembrow et al, 2010; Gee et al, 2012; Lee et al, 2014; Leyrer‐Jackson and Thomas, 2019). Owing primarily to high expression of hyperpolarization‐activated cation (HCN) channels (Salling et al, 2018; Shah, 2014), the membrane potential of type A neurons undergoes a rebound depolarization following negative current injections, often described as a “hyperpolarization sag.” Type B neurons, instead, generally lack this pronounced sag current.…”
mentioning
confidence: 99%